Historical Islamic TV as Storytelling-Based Educational Media for Early Childhood Cognitive Development - Ma'rifatul Azizah Putri Anggraeni; Mursid (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2025)
This study aims to describe the use of Historical Islamic TV as storytelling-based educational media in supporting early childhood cognitive development and to explore children’s cognitive responses during learning activities. This research was conducted at RA Al-Hidayah in Semarang and used a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving 15 children aged 5-6 years in group B. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings show that Historical Islamic TV media attracts children’s attention and encourages active participation during storytelling sessions. Children were able to recognize Islamic historical figures, particularly Ali bin Abi Thalib, recall story sequences, and respond verbally to teacher questions. The use of puppets and visual storytelling supported children’s memory and understanding of simple historical narratives. Therefore, Historical Islamic TV can serve as an alternative storytelling-based educational medium that integrates cognitive stimulation and Islamic values in early childhood learning.